اللباس النوميدي من خلال الانصاب ذات المشاهد الايكونوغرافية عنوانا للهوية و الاصالة - بوشارب, سلوى (University of Eloued جامعة الوادي, 2022)
يتناول هذا الموضوع أحد العناصر الأساسية المكونة لهوية لمجتمع النوميدي هو اللباس الذي تغير البعض منه من حيث مادة صنعه وشكله حسب المراحل التاريخية التي مر بها شمال افريقيا القديم في حين بقي البعض الآخر محافظا على شكله العام بالرغم من وجود بعض التعديلات البسيطة عليه، هذه الأخيرة التي كانت دليلا على تعرض بعض النماذج منه للتطور الذي شهدته حرفة و فن الخياطة عموما و هذا ما وقفت عليه من خلال دراستي البسيطة لكلا الصنفين منه والتي لا تزال العديد من الأنصاب ذات المشاهد الايكونوغرافية محتفظة بها و هذا دليل كاف على أهمية فن النحت ودوره في عملية التأريخ المرتبطة بالنشاط الانساني في جميع المجالات ومن ثمة رسم صورة واضحة المعالم عن طبيعة البناء الحضاري له عبر العصور. This topic deals with one of the basic elements that constitute the identity of the Numidian society, which is the dress, some of which have changed in terms of material and shape according to the historical stages that ancient North Africa went through, while others remained preserving their general form despite the presence of some minor modifications to it. It was evidence of the exposure of some models of it to the development witnessed by the craft and the art of sewing in general, and this is what I found through my simple study of both types of it, which still many monuments with iconic scenes preserved, and this is sufficient evidence of the importance of the art of sculpture and its role in the process of history Associated with human activity in all fields, thus drawing a clear picture of the nature of the civilizational construction of it through the ages.